Municipal Social Responsibility of Statutory Cities in the Czech Republic - Tetřevová, Liběna; Jelínková, Martina (MDPI AG (Multidisciplinary Digital Publishing Institute), 2019)
The article presents the results of a study, the objective of which was to identify the socially responsible practices applied by the statutory cities in the Czech Republic, in order to analyse and evaluate the scope and structure of socially responsible activities performed by them and communicated on the internet.
Společenská odpovědnost municipalit z pohledu statutárních měst České republiky
Keywords: municipal social responsibility; municipal stakeholders; socially responsible activities; socially responsible communication; Czech Republic; Pardubice City; společenská odpovědnost municipalit; zainteresované strany municipalit; společensky odpovědné aktivity; společensky odpovědné komunikování; Česká republika; město Pardubice